1 Laws of New Hampshire: Province Period 221-22 (Albert Stillman Batchellor ed., 1904) - (:unkn) unknown (My University, 1687)
Demanded "that no person whatsoever above Sixteene yeares of age remaine unlisted." Equipment was "a well fixed musket" with a barrel at least three feet. The caliber was large: "the bore for a bullett of twelve to the pound." Also necessary were bandoliers and a cartridge box, plus bullets and powder. Officers had the option of allowing their men to have "a good pike and sword" instead of the musket. As for horsemen, "every soldier belonging to the horse" had to bring "a good serviceable horse covered with a good saddle with holsters breastplate and crupper a case of good pistolls and sword and halfe a pound of powder and twenty sizable bulletts . . . And every trooper have at his usuall place of abode a well fixed Carabine with belt and swivel.
Keywords: MILITIAS